2023
DOI: 10.3389/fenrg.2023.1088742
|View full text |Cite
|
Sign up to set email alerts
|

Phase field modeling microstructural evolution of Fe-Cr-Al systems at thermal treatment

Abstract: A phase field model to study dynamics of microstructure transformations and the evolution of defect structure during heat treatment of Fe-Cr-Al systems is developed. Statistical and kinetic properties of evolving microstructure and defect structure in alloys with different content of alloying elements and at different temperatures were studied. Point defects rearrangement during precipitation is discussed in details. Universality of statistical distributions over precipitate size is revealed for considered cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Here two stages related to precipitate formationand-growth and their coarsening are well observed. Precipitates start to form above the critical time t c depending on the condition of thermal treatment and composition of the alloy as was discussed in [65]. It is seen that mean precipitate size increases up to 4 nm at large times and the corresponding number density is around (2 − 3) × 10 24 m −3 that relates well to experimental observations for these two quantities [10][11][12][13].…”
Section: Modeling Microstructure Evolution At Thermal Treatmentsupporting
confidence: 71%
See 1 more Smart Citation
“…Here two stages related to precipitate formationand-growth and their coarsening are well observed. Precipitates start to form above the critical time t c depending on the condition of thermal treatment and composition of the alloy as was discussed in [65]. It is seen that mean precipitate size increases up to 4 nm at large times and the corresponding number density is around (2 − 3) × 10 24 m −3 that relates well to experimental observations for these two quantities [10][11][12][13].…”
Section: Modeling Microstructure Evolution At Thermal Treatmentsupporting
confidence: 71%
“…It was shown that the main source of complexity of such systems is in the non-monotonic dependence on Cr concentration of large number of quantities and properties characterising its thermodynamic behaviour and its response to irradiation. A comprehensive research strategy, as outlined in [19], has been developed for FeCrAl systems, especially to study kinetics of the nano-sized a¢-phase [20][21][22]. This strategy combines various techniques, including ab-initio calculations, CALPHAD modeling, and experiments.…”
Section: Introductionmentioning
confidence: 99%